TECHNOLOGIES FOR DEVELOPING STUDENT'S COMMUNICATIVE COMPETENCE IN ENGLISH CLASSES - Jo‘rayeva Muazzam Madamin qizi (Journals Park Publishing, 2025)
Technologies for developing students' communicative competence are important in English classes. Today, along with the expansion of global communication and intercultural dialogue, the need to develop students' communicative competence in the process of learning English is increasing. This article provides information about the technologies and methods used to develop students' communicative competence in English language classes.
Keywords: English language, linguistics, pragmatics, competencies, methods, technologies.